Representing mass violence : conflicting responses to human rights violations in Darfur - Savelsberg, Joachim J., 1951- (University of California Press, 2015)
"How do UN Security Council and International Criminal Court interventions, both part of the Justice Cascade, color representations of mass violence? What images of suffering and of responsible actors arise instead from the humanitarianism and diplomacy fields? How are these competing perspectives communicated to the public via mass media? Zooming in on the case of Darfur, Joachim J. Savelsberg analyzes over three thousand news reports and opinion pieces and interviews leading newspaper correspondents, NGO experts, and foreign ministry officials from eight countries to show the dramatic differences in the framing of mass violence around the world and across social fields. Representing Mass Violence contributes to our understanding of how the world acknowledges and responds to violence in the Global South"--Provided by publisher.